2019
DOI: 10.17582/journal.aavs/2019/7.s2.44.50
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Extrahepatic Cholestasis in Dogs: Ultrasonographic, Biochemical and Histopathological Study

Abstract: To explore the role of ultrasound in the diagnosis of extrahepatic cholestasis in dogs, an experimental extrahepatic cholestasis was done successfully in seven male mongrel dogs via common bile duct ligation that mimic natural cases in dogs. All observations and changes were recorded post-operative; clinical, biochemical and ultrasonography. All dogs showed jaundice, orange colored urine and clay feces in the 3 rd day post-operative. Significant increase in serum levels of AST, ALT, GGT, ALP, total and direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In the current study, the animals showed various degrees of hepatic dysfunction, and these results were in accordance with previous study conducted by Otte et al and Gomaa et.al. [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the animals showed various degrees of hepatic dysfunction, and these results were in accordance with previous study conducted by Otte et al and Gomaa et.al. [36,37].…”
Section: Discussionmentioning
confidence: 99%